IoT Based Smart Metering Mirror System for Monitoring Electric Bills - Md. Ruman, Sharea Takreem, Asadulla Khan Lodi, Omer Farooz (Mathematical Statistician and Engineering Applications, 2023)
This project proposes an IoT-based smart metering mirror system designed to monitor electric bills and enhance power efficiency. The system leverages the capabilities of IoT devices, along with integration with the Telegram application, to provide real-time monitoring and control of electricity consumption. Additionally, a prepaid units feature is incorporated to promote power efficiency and enable users to better manage their energy consumption. The smart metering mirror system utilizes IoT sensors and a microcontroller to gather electricity consumption data from the utility meter. This data is then transmitted wirelessly to a central server for processing and analysis. Through the integration with the Telegram application, users can conveniently access and monitor their electricity usage, billing information, and related insights on their smart phones or other devices. To encourage power efficiency, the system incorporates a prepaid units feature. Users can purchase a predetermined amount of electricity units in advance, which are deducted based on their consumption. The system provides real-time updates on the remaining units, allowing users to track and adjust their electricity usage accordingly. Notifications and alerts can be sent through the Telegram application to inform users about their consumption patterns and remind them to conserve energy. Furthermore, the integration with the Telegram application provides a user-friendly and accessible interface for interacting with the system. Users can easily view their consumption data, billing history, and prepaid units information through the familiar Telegram platform. The system’s real-time notifications and alerts enhance user engagement and promote proactive energy management. In summary, the IoT-based smart metering mirror system presented in this project offers an innovative approach to monitor electric bills and improve power efficiency. By leveraging the capabilities of IoT devices and integration with the Telegram application, users can conveniently access and analyze their electricity consumption data, while the prepaid units feature encourages responsible energy usage. This system has the potential to empower users to make informed decisions, reduce energy waste, and optimize their electricity bills.